2020
DOI: 10.1177/0956462420951501
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of PrEP use and effective contraceptive use among East African women in HIV serodiscordant partnerships

Abstract: Women who have a prevention mindset may opt for concurrent use of oral pre-exposure prophylaxis (PrEP) and all forms of contraception; we therefore assessed how contraception may influence PrEP use or vice versa. We analyzed data from Kenyan and Ugandan HIV-uninfected non-pregnant women in sero-discordant partnerships who were participating in the Partners Demonstration Project. Using multivariable generalized estimating equation models, we estimated the associations between effective contraceptive use and 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Emerging studies of PrEP use among adolescent girls, and young women have mixed results, although most note high PrEP initiation and declining use over time (66)(67)(68)(69)(70). The high uptake and sustained adherence observed in this study are consistent with a recent periconception study conducted among HIV-negative Kenyan women within a serodifferent partnership and desire to have a child (27).…”
Section: Discussionsupporting
confidence: 75%
“…Emerging studies of PrEP use among adolescent girls, and young women have mixed results, although most note high PrEP initiation and declining use over time (66)(67)(68)(69)(70). The high uptake and sustained adherence observed in this study are consistent with a recent periconception study conducted among HIV-negative Kenyan women within a serodifferent partnership and desire to have a child (27).…”
Section: Discussionsupporting
confidence: 75%
“…Emerging studies of PrEP use among adolescent girls, and young women have mixed results, although most note high PrEP initiation and declining use over time [79][80][81][82][83]. The high uptake and sustained adherence observed in this study are consistent with a recent periconception study conducted among HIV-negative Kenyan women within a serodifferent partnership and desire to have a child [27].…”
Section: Plos Medicinesupporting
confidence: 73%
“…A study by Ngure et al which integrated PrEP with FP services found that PrEP dispensation was more frequent among those concurrently using effective contraception, (adjusted relative risk (aRR)=1.19; 95% CI =1.08 to 1.32) and contraceptive use was more common among those on PrEP (aRR 1.63; 95% CI 1.18 to 2.25), highlighting the importance of SDMs that integrate PrEP with FP services. 32 Pintye et al found that participants who initiated PrEP at MCH clinics took an additional 18 min for PrEP related activities over and above the time spent at the clinic to receive routine MCH services. The additional time could deter AGYW from initiating and continuing PrEP and depending on healthcare facility size and patient volume integrating PrEP into these routine services could result in several additional hours of work for nurses.…”
Section: Resultsmentioning
confidence: 99%
“…These studies used nurses dedicated to providing PrEP services only, which may limit applicability in a sub-Saharan setting where facilities have a limited clinical workforce. A study by Ngure et al which integrated PrEP with FP services found that PrEP dispensation was more frequent among those concurrently using effective contraception, (adjusted relative risk (aRR)=1.19; 95% CI =1.08 to 1.32) and contraceptive use was more common among those on PrEP (aRR 1.63; 95% CI 1.18 to 2.25), highlighting the importance of SDMs that integrate PrEP with FP services 32. Pintye et al found that participants who initiated PrEP at MCH clinics took an additional 18 min for PrEP related activities over and above the time spent at the clinic to receive routine MCH services.…”
Section: Resultsmentioning
confidence: 99%